Dyadically Expanded States of Consciousness and Therapeutic Change in the Interaction Between Analyst and Adult Patient. Issue 5 (2nd September 2016) - Cavelzani, Alessandro; Tronick, Ed
Abstract : This paper presents a discussion of the mutual regulation model and the dyadic expansion of consciousness model as a way to better understand the interaction between the analysand and analyst and the process of therapeutic change. We argue that by examining matching, mismatching, and in particular reparation of therapeutic exchanges at the micro-level as well as the macro-level of the therapeutic exchange, including whole sessions or even over multiple sessions provides insight in the establishment of the therapeutic relationship and the formation of Dyadic States of Consciousness. Clinical examples are presented.